Continuing respiratory problems three and a half years after acute viral bronchiolitis. - Webb, M S (1985)
We reviewed the clinical progress of 81 children as part of a prospective study three and a half years after admission to hospital with acute viral bronchiolitis in infancy. Fifty six (69%) reported episodes of lower respiratory symptoms continuing over the preceding year, 25 (31%) had symptoms lasting for longer than two weeks on two or more occasions, 14 (17%) had symptoms for more than 100 days, and six (7%) required readmission to hospital with acute respiratory illness. Two years previously, these percentages had been 82%, 36%, 33%, and 13% respectively. Forty six (57%) children were said to be improving or to have become asymptomatic, but eight (10%) were deteriorating. There was no difference in the personal or family history of atopy, nor in the rate of skin test positivity between those with and without continuing symptoms, suggesting that atopy does not play an important role in the persistence of symptoms. Less than half the symptomatic children had received bronchodilator treatment during the preceding 12 months.